Raising geese - Bidima, I.M. (Technical Centre for Agricultural and Rural Cooperation, 2014)
With their meat, liver, feathers and down much sought after, raising geese can be a highly profitable venture. This practical, colourfully illustrated guide provides tips and guidance for breeding geese. With liberal use of tables and easy-to-follow processes, topics covered include anatomy, physiology and rearing techniques, with emphasis placed on feeding and common diseases. Later sections of the guide set out valuable ideas for the marketing of geese, as well as some recipes.